AN OVERVIEW OF ETHNOMEDICINE AND FUTURE ASPECT OF ETHNOMEDICINAL PLANTS - Rishi, *Arya; D.C, Singh; R.C, Tiwari; B.M, Tripathi (International Journal of Ayurveda and Pharma Research, 2016)
Ethno botanical study is now of immense importance in the field of medical science, it is well established branch of science with much attention. Ethno botany is the scientific relationships that exist between people and plants. Traditional medicine and ethno botanical information play an important role in scientific research, particularly when the literature and field work data have not been properly evaluated. Globally, about 80% of the traditional medicines used for primary health care are derived from plants. In China, traditional medicine accounts for around 40% of all health care delivered. In Chile 71% of the population, and in Colombia 40% of the population, have used such medicine. India is one of the twelve mega-biodiversity countries of the world having rich vegetation with a wide variety of plants with medicinal value. Rural people not only depend on wild plants as sources of food, medicine, fodder and fuel, but have also developed methods of resource management, which may be fundamental to the conservation of some of the world’s important habitats. In India, 65% of the populations in rural areas are using medicinal plants to meet their primary health care needs. Here a review on ethnomedicine including correlation of Ethnomedicine and Ayurveda will be mentioned. Attention should be made for proper exploitation, utilization and further reasearches on ethno medicinal important plant species.